Punctuation and Capitalization in Writing: How Do Students Produce Them? - Mega Mulianing Maharani; Emy Sholikhatun (Universitas Islam Sultan Agung, 2022)
This study aimed to know the way the students produce punctuation and capitalization in their writing of descriptive text. The students as the respondents of this study were 38 eleventh graders a certain senior high school in Semarang. They were given a descriptive text writing test. Their writing test result was the data of this present study. The data were analyzed by using the rule of punctuation and capitalization writing. The analyzed data were interpreted to get the final conclusion of the study. The results of the study were that the students’ incorrect writing of punctuation was on comma, full stop and apostrophe, while for capitalization was on the first word of a sentence, the name of people, and the names of places. In short, the researchers classified the ways the students wrote descriptive text were incorrectly on comma, full stop, apostrophe, the first word of a sentence, the name of people, and the names of places.